The Influence of Organizational Culture, Whistleblowing System, and Internal Control System for Prevention Fraud - Vidya Nuraini; Fauziyah Fauziyah; Beby Hilda Agustin (Dinasti Publisher, 2025)
Fraud prevention in organizations is one of the main focuses in risk management, especially in the era of increasingly complex globalization and digitalization. This research investigated the impact of organizational culture, whistleblowing systems, and internal control systems on fraud prevention at PT Pos Indonesia, Pare Branch in 2025. Employing a quantitative methodology, primary data were collected through questionnaires distributed to employees and subsequently analyzed using SPSS version 25. The findings revealed a significant positive correlation between organizational culture, whistleblowing systems, and internal control systems in mitigating fraud. These three elements exhibit a synergistic relationship, where a conducive organizational culture fosters the effectiveness of both whistleblowing and internal control mechanisms. Conversely, robust internal controls and a functional whistleblowing system reinforce an ethical organizational environment. Effective collaboration between these three elements creates an environment that supports fraud prevention and increases trust, integrity, and morale.